COVID-19 induced psychosis: A case report. (February 2023) - Ellini, Sana; Romdhane, Imen Ben; Bougacha, Dhouha; Abassi, Ameni; Cheour, Majda; Damak, Rahma
Highlights: We present the case of a patient with a COVID-19 infection discovered by severe paranoid psychiatric manifestations associated with biological disturbances, without any specific physical sign or orientation towards COVID-19. Through the presentation of this clinical case, we emphasize the interest of actively seeking a COVID-19 infection in the context of a pandemic in front of any unusual or acute psychiatric manifestation not explained by other factors and pushing the investigations to the slightest suspicion of COVID-19 infection.